Contribution to the scythridid fauna of southern Buryatia, with description of seven new species (Lepidoptera: Scythrididae) - Nupponen, Kari (Entomologica Fennica, 2003)
A list of 26 species embracing 673 specimens of the family Scythrididae collected during 13.–29.VI.2002 from southern Buryatia is presented. Seven new species are described: Scythris erinacella sp. n., S. gorbunovi sp. n., S. hamardabanica sp. n., S. malozemovi sp. n., S. ninae sp. n., S. potatorella sp. n. and S. sinevi sp. n. Two unknown species are mentioned but not described because only females are available. In addition, S. penicillata Chrétien, 1900 is reported as new for Russia, S. emichi (Anker, 1870) as new for the Asiatic part of Russia and seven further species as new for the Baikal region. The known distribution range of each species is given as well as further notes on some poorly known taxa.